La competitividad de las empresas de transporte público urbano y su influencia en la satisfacción de los usuarios del servicio, en la ciudad de Huamachuco, período 2015 - 2017 - Blas Ríos, Carmen Janeth (2017)
The present thesis was carried out in the city of Huamachuco, province of Sánchez Carrión, La Libertad Region, Peru; being the subject of interest the urban transport sector. Its main objective was to determine how the Competitiveness of urban public transport companies influences the satisfaction of users of the service in the city of Huamachuco. In analyzing the problematic reality, the research problem was formulated: How does the Competitiveness of urban public transport companies influence the Satisfaction of the users of the service, in the city of Huamachuco, period 2015 - 2017? For the collection of data, three populations have been taken into account: 37 drivers of the vehicles of both companies, 6041 users and two managers of both companies; Considering the sample the same for the population of drivers and managers of transport companies and for users was 288; To the first two populations a survey was applied and for the third they were interviewed. The results obtained have allowed the corresponding discussion to be carried out, demonstrating the validity of the hypothesis: "The competitiveness of urban public transport companies has a positive and significant influence on the satisfaction of users of the service in the city of Huamachuco, period 2015 - 2017 ". The main conclusion is that the Competitiveness of urban public transport companies and User Satisfaction maintain a strong and significant positive correlation demonstrated by the Pearson correlation coefficient (r = 0.774), as well as the level of competitiveness of the companies. Transport is at a "medium low" level, as some of its factors or items are presented as weaknesses. In the face of this, it is recommended that weaknesses be overcome such as expanding routes within the city, selecting staff (drivers and collectors) with a minimum of secondary instruction, reviewing and respecting schedules of vehicle shifts, improving Staff fees based on merits, and incorporate new vehicle units that are in good repair and modernity.